2017
DOI: 10.1002/bdr2.1092
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive and Neurobehavioral Effects of Ethiprole Administered to Mice in the Diet

Abstract: The dose levels of ethiprole in the present study produced several adverse effects in neurobehavioral parameters in mice. Birth Defects Research 109:1568-1585, 2017. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
(40 reference statements)
1
9
0
Order By: Relevance
“…For exploratory behavior in the F 1 generation, the number of horizontal activities increased significantly in the high‐dose group and the average speed decreased significantly in all treatment groups for exploratory behavior in female offspring at three weeks of age. In the previous study (Tanaka & Inomata, ), the average speed showed a significant tendency to be decreased in treatment groups for exploratory behavior in male offspring at three weeks of age, and the number of horizontal activities significantly increased in treatment groups of female offspring at three weeks of age.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…For exploratory behavior in the F 1 generation, the number of horizontal activities increased significantly in the high‐dose group and the average speed decreased significantly in all treatment groups for exploratory behavior in female offspring at three weeks of age. In the previous study (Tanaka & Inomata, ), the average speed showed a significant tendency to be decreased in treatment groups for exploratory behavior in male offspring at three weeks of age, and the number of horizontal activities significantly increased in treatment groups of female offspring at three weeks of age.…”
Section: Discussionmentioning
confidence: 62%
“…In the previous study (Tanaka & Inomata, ), the route and time of olfactory orientation showed significant tendencies to be accelerated in treatment groups (0.0003–0.0027% in the diet) of female offspring on PND 14. These results suggest that ethiprole treatment produced similar effects on similar variables of behavioral development in either sex.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations